Justice et infra-justice en Nouvelle-France. Les voies de fait à Montréal entre 1700 et 1760 - Leclerc, Jean-François (Criminologie, 1985)
It has become obvious in the past several years that the judicial statistics have certain limitations as far as reconstructing the evolution of crime under the Ancien Régime is concerned. The administrative inadequacies of the institutional justice of that era, its insufficient means of intervention, invite caution, but the existence of infra-judicial mechanisms for dealing with crime lead to the conclusion that only a fraction of the crimes ever came before the courts. Our research on trials for assault and battery heard in the jurisdiction of Montreal between 1700 and 1760 revealed several cases establishing the existence in New France, and confirming the observations of Alfred Somanfor France, of practices according to which the institution of proceedings by certain victims was often in order to start a process of negotiation with the aggressor or force him to come to an agreement out of court, which usually put an end to the procedures. Since there is rarely any explicit mention of agreements reached, even in the notarial archives, we arrived at the possibility that the dropping of legal proceedings indicated an infra-judicial settlement of the case. This led us to analyse the decrease in the number of trials for assault and battery in Montreal after 1730. It was not because of the usual explanation, that it was a sign of a “decrease in crime”, but rather due to a strengthening of the infra-judicial system, particularly in the rural areas, where there was less recourse to the authority of the royal court to settle minor infractions.